191k views
1 vote
Multiply.
3y^2(-5y^4)
Simplify your answer as much as possible.

1 Answer

1 vote

Answer:


\boxed{\sf{-15y^6}}

Explanation:

To solve this, you have to use a distributive property to multiply the numbers from left to right.

Distributive property:

A(B+C)=AB+AC

A(B-C)=AB-AC


\sf{3y^2\left(-5y^4\right)=-3y^2* 5y^4}

Multiply.

-3*5=-15

-15y²y⁴


\sf{y^2y^4=y^2^+^4=y^6}

=-15y⁶

Therefore, the final answer is -15y⁶.

I hope this helps, let me know if you have any questions.

User Giuliolunati
by
4.1k points